Unsteady Couette-Poiseulle Flow with Temperature Dependent Physical Properties In The Presence Of a Uniform Magnetic Field - A. Attia, Hazem (Malaysian Journal of Science, 2005)
The unsteady magnetohydrodynamic MHD Couette-Poiseulle flow and heat transfer of an electrically conducting fluid is studied in the presence of a transverse uniform magnetic field with temperature dependent viscosity and thermal conductivity. The fluid is subjected to a constant pressure gradient and an external uniform magnetic field perpendicular to the plates which are kept at different but constant temperatures. The effect of the magnetic field, the temperature dependent viscosity and thermal conductivity on both the velocity and temperature fields is reported.